INTEGRASI USAHATANI DENGAN PEMANFAATAN LIMBAH TERNAK DI DESA SAPEN, MOJOLABAN, SUKOHARJO - Pratama, Yogi Pasca; Samudro, Bhimo Rizky; Soesilo, Albertus Maqnus; Sarungu, Julianus Johnny; Irawan, BRM Bambang (Universitas PGRI Yogyakarta, 2019)
Integrated aquaculture management systems, aquaculture, and crop cultivation can be implemented in synergy where each business that supports each other, supports each other, support each other, by optimally utilizing the potential resources needed. Sapen Village, Mojoaban District, Sukoharjo Regency chose the location of empowerment because it has the potential for integrated farming. Livestock waste that is diverted and converted into pollution sources, on the other hand, the fishery business is very dependent on pellet feed, it is agreed that integration will occur, so the problem of livestock waste can be solved by presenting natural food sources for the fishing business. The program carried out is the socialization of alternative animal feed selection and the socialization of how to make alternative feed. The selection of alternative fish feed, besides being able to incur fish farmers' production costs, is also a form of integration between cattle and goat groups and fish livestock groups. From the implementation of this community service program, it will gain new knowledge about the management of agricultural waste by developing earthworm (lumbricus rubelius) cultivation as fish feed ingredients. Besides, the public also gained new knowledge about how to process livestock as an alternative to fish food.Keyword: integrated farming systems, livestock waste breeding, alternative fish feed